Performance of pearlmillet [Pennisetum glaucum (L). R. Br.] variety MPMH-17 in Jodhpur District under rainfed condition: ASSESSMENT OF PEARL MILLET VARIETY MPMH-17 IN ARID ZONE - Tewari, Pratibha (Annals of Arid Zone, 2024)
Frontline demonstrations (FLD) were conducted in various villages of Jodhpur to showcase the substantial impact of improved crop production technologies on pearl millet yield during kharif 2022-23. The improved technologies, represented by the use of pearl millet hybrids (MPMH-17) along with the recommended dose of fertilizers (60 kg N + 30 kg P2O5 ha-1), were assessed by comparing them to farmers’ practices (Local landrace grown without fertilizers) both under rainfed (53) and irrigated (80) conditions. The mean grain yield with farmers’ practice under rainfed conditions varied from 0.67 to 0.76 t ha-1 but of MPMH-17 varied from 1.03 to 1.18 t ha-1. Corresponding values under irrigated conditions were 0.78 to 0.93 and 1.24 to 1.37 t ha-1 for farmers’ practice and MPMH-17, respectively. Hybrid MPMH-17 exhibited the average extension grain and straw yields gap of 0.40 and 1.36 t ha-1 under rainfed and 0.44 and 1.58 tha-1 under irrigated conditions, respectively. Values of technology gap and technology index in grain yield of MPMH-17 were 1.73 t ha-1 and 61.02% in rainfed condition and 1.53 t ha-1 and 54.09% in irrigated condition and corresponding values for straw yield were 3.57 t ha-1 and 55.82% in rainfed condition and 3.05 t ha-1 and 47.71% in irrigated condition. Average additional returns were Rs. 20481 under irrigated and Rs 16643 under rainfed conditions.